Effects of inositol in women with polycystic ovary syndrome: an umbrella review of meta-analyses from randomized controlled trials - Duan, Mengxue; Yang, Min; Li, Chang; Wu, Xiao; Yin, Xiaoxiao; Zhu, Hongqiu (Frontiers in Endocrinology, 2026)
ObjectivesThis umbrella review aimed to synthesize and appraise the evidence regarding the efficacy of inositol for Polycystic Ovary Syndrome (PCOS) by integrating meta-analyses of randomized controlled trials(RCTs), thereby assessing the robustness of the existing body of evidence.MethodsWe searched four databases from inception to August 2025 for relevant RCT meta-analyses. Primary outcomes included hormonal profiles, glycolipid metabolism, anthropometrics, and reproductive outcomes. Quality was assessed using AMSTAR-2 and GRADE.ResultsThirteen meta-analyses were included. AMSTAR-2 ratings were 23.1% high, 53.8% low, and 23.1% very low quality. GRADE assessment of 85 evidence items revealed no high-quality evidence; 18.9% were moderate, 40% low, and 41.1% very low quality. Pooled analyses demonstrated that inositol significantly improved multiple outcomes compared to placebo/FA: it reduced serum luteinizing hormone (LH: MD -3.43 IU/L, 95% CI [-4.29, -2.56], P < 0.00001), total testosterone (TT), free testosterone (FT: MD -0.02 nmol/L, 95% CI [-0.02, -0.01], P < 0.00001), improved sex hormone-binding globulin (SHBG: MD 36.72 nmol/L, 95% CI [28.52, 44.91], P < 0.00001), and androstenedione. Benefits were also observed for homeostatic model assessment of insulin resistance (HOMA-IR: MD -1.14, 95% CI [-1.35, -0.94], P < 0.00001), fasting insulin (FI: MD -23.40 pmol/L, 95% CI [-32.80, -14.01], P < 0.00001), triglycerides, and reproductive outcomes (live births: Risk Ratio [RR] 2.29, 95% CI [1.07, 4.93], P = 0.03; ovulation rate: RR 2.75, 95% CI [1.71, 4.41], P < 0.0001). However, versus metformin(MET), its effects on most parameters were not significant, except for triglycerides and pregnancy rates. Cross-subgroup analysis of inositol subtypes indicated MI/MI+FA was superior for metabolic and reproductive outcomes, while D-chiro-inositol monotherapy should be used with caution in clinical practice; combination therapy did not consistently outperform monomers.ConclusionInositol improves core PCOS manifestations. Supported by moderate-quality evidence for effects on TT, FT, SHBG, HOMA-IR, and pregnancy/ovulation rates, it is a promising therapy. Differential efficacy of inositol subtypes may inform personalized treatment. However, outcomes based on low-quality evidence require cautious interpretation and should not solely guide clinical decisions, highlighting the need for larger, rigorous trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251146691.